HAK DASAR WARGA BINAAN LEMBAGA PEMASYARAKATAN KHUSUS PEREMPUAN KELAS II A JAKARTA: Basic Right Of Class II A Prison Citizen For Woman In Jakarta - Dwi Septiani; Wahyuni Retno Wulandari (Reformasi Hukum Trisakti, 2025)
Reproductive rights are the basic rights of every individual to make decisions freely and responsibly regarding their reproductive health. The practice this right has not been fully realized, as experienced by female inmates at the Class II A Jakarta Women's Penitentiary. The main problems in this study are: 1) How are the arrangements for fulfilling basic rights facilities (reproductive rights, in this case including family visits) for women in the Class II A Jakarta Women's Penitentiary reviewed based on CEDAW and Law Number 22 of 2022 concerning Corrections? 2) How is the implementation of the arrangement for fulfilling basic rights facilities (reproductive rights, including family visits) for women in the Class II A Jakarta Women's Penitentiary reviewed based on CEDAW and Law Number 22 of 2022 concerning Corrections? The research method used is socio-legal. The results of the study show that in the Class II A Women's Special Penitentiary in Jakarta there are no facilities for fulfilling reproductive rights (family visits) because there are no laws and regulations that specifically explain that the basic rights of inmates also include reproductive rights (family visits). Meanwhile, inmates feel the need for facilities to fulfill these reproductive rights.